Strengthening Chemistry Teachers' Technological Pedagogical Content Knowledge through the Introduction of Augmented Reality and Learning Management Systems - Muhamad Imaduddin; Andari Puji Astuti (Bulletin of Community Engagement, 2022)
Strengthening of Technological Pedagogical Content Knowledge (TPACK) needs to be done as an effort to present chemistry learning that is following the times. The purpose of this activity is to identify the TPACK conditions of chemistry teachers, as well as to seek initial activities to strengthen teachers’ TPACK through the introduction of augmented reality technology according to chemical content, as well as classroom management based on a learning management system platform. The implementation method included Focus Group Discussion (FGD) activities, lectures, and implementation practices. Participants in this activity consisted of chemistry teachers who were active members of the Chemistry Teacher Groups of Kudus Regency, as many as 17 teachers. This community service activity is in the form of a series of activities that include (1) identification of difficult chemistry materials, most of which show microscopic concepts as one of the difficult materials, (2) identification of the condition of the teacher's level of mastery of technology which is generally still at a moderate level, (3) introduce the potential use of technology in the chemistry learning process in the form of Augmented Reality, namely RAppChemistry, and (4) the use of a learning management system in the form of the Google Classroom platform that can be used in electronic-based teaching and learning processes. Further partnerships need to be implemented to implement the technology on a classroom scale. Activities that may be carried out are lesson study activities to optimize the integration of technology in chemistry learning. Keywords: Pedagogical Content Knowledge, Augmented Reality, Learning Management System